1994
DOI: 10.1152/ajpregu.1994.266.5.r1599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal denervation on postprandial sodium excretion in experimental heart failure

Abstract: The hormonal, hemodynamic and renal excretory changes after an oral load of sodium were examined in renal-denervated dogs with an arteriovenous (AV) fistula and the syndrome of compensated high-output heart failure. After ingestion of a meal containing 125 meq of sodium, the total postprandial urinary sodium excretion and fractional sodium excretion were approximately twofold higher in the renal-denervated AV fistula dogs, compared with a control group with intact renal nerves (P < 0.05). The postprandial elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…The investigation revealed that sodium retention was attributable in part to renal sympathetic efferent nerve activity, which was abolished by renal nerve ligation. On the basis of measurements of postprandial sodium excretion, similar conclusions were reached from work on renal denervated dogs with an arteriovenous fistula and the syndrome of compensated high-output heart failure 44 ; however, long-term ventricular pressure was not monitored in these models. The ligation of renal nerves protected against expression of postprandial natriuretic resistance and the development of congestion or rises in ventricular filling pressures.…”
Section: Postmyocardial Infarction and Congestive Heart Failurementioning
confidence: 65%
“…The investigation revealed that sodium retention was attributable in part to renal sympathetic efferent nerve activity, which was abolished by renal nerve ligation. On the basis of measurements of postprandial sodium excretion, similar conclusions were reached from work on renal denervated dogs with an arteriovenous fistula and the syndrome of compensated high-output heart failure 44 ; however, long-term ventricular pressure was not monitored in these models. The ligation of renal nerves protected against expression of postprandial natriuretic resistance and the development of congestion or rises in ventricular filling pressures.…”
Section: Postmyocardial Infarction and Congestive Heart Failurementioning
confidence: 65%
“…We did not measure plasma levels of ANP or renin activity. Previous studies 8,11 have shown that RD did not significantly affect plasma ANP. In the present study, however, the plasma ANP level 4 weeks after the operation may be lower in MI rats with RD than in those with INN, since LV end-diastolic pressure was lower in MI rats with RD.…”
Section: Effects Of Rd On LV Functionmentioning
confidence: 75%
“…In the present study, however, the plasma ANP level 4 weeks after the operation may be lower in MI rats with RD than in those with INN, since LV end-diastolic pressure was lower in MI rats with RD. No significant changes in plasma renin activity induced by RD were observed, 11,13 whereas significant reduction in renin activity has been reported. 31 If the latter is true, RD may reduce the effects of angiotensin II and aldosterone on ventricular structure and function.…”
Section: Effects Of Rd On LV Functionmentioning
confidence: 75%
See 1 more Smart Citation
“…Percutaneous renal sympathetic denervation may be particularly beneficial in this setting and indeed complementary to β-adrenoceptor blockade given differing pathways of sympathetic abrogation.This is supported by animal studies which have demonstrated improved cardiac function and reduced pathological fibrosis following denervation [33,34]. Furthermore, denervation has improved renal blood flow in the (preclinical) heart failure setting and this may have significant implications for the cardiorenal syndrome [35]. A small pilot study of seven patients with chronic mild to moderate systolic heart failure (mean EF 43 ± 15%) did not raise any procedural or safety concerns [36], in particular no major drop in BP despite low baseline levels and no change in renal function, with a mild improvement in the 6 min walk test.…”
Section: Figurementioning
confidence: 84%